PsycEXTRA Dataset 2006
DOI: 10.1037/e539672012-001
|View full text |Cite
|
Sign up to set email alerts
|

The Literacy of America's College Students

Abstract: Rapid changes in technology make it necessary for adults of all ages to use written information in new and more complex ways. For example, learning how to operate computers, filling out complicated tax forms, and comparing price labels when shopping for groceries are just a few of the many tasks that are important parts of our lives.Every adult needs a range of literacy skills to achieve his or her personal goals, pursue a successful career, and play an active role as a citizen. High levels of literacy also en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 0 publications
5
20
1
Order By: Relevance
“…Results revealed that students at four-year institutions performed significantly higher than students at two-year institutions. These results are consistent with previous research (Baer et al 2006;Liu and Roohr 2013). For instance, results from the National Survey of America's College Students (NSACS), which used the National Assessment of Adult Literacy (NAAL) to measure quantitative literacy, also showed students at four-year institutions outperforming their peers at two-year institutions (Baer et al 2006).…”
Section: Performance Differences Across Subgroupssupporting
confidence: 82%
See 3 more Smart Citations
“…Results revealed that students at four-year institutions performed significantly higher than students at two-year institutions. These results are consistent with previous research (Baer et al 2006;Liu and Roohr 2013). For instance, results from the National Survey of America's College Students (NSACS), which used the National Assessment of Adult Literacy (NAAL) to measure quantitative literacy, also showed students at four-year institutions outperforming their peers at two-year institutions (Baer et al 2006).…”
Section: Performance Differences Across Subgroupssupporting
confidence: 82%
“…These results are consistent with previous research (Baer et al 2006;Liu and Roohr 2013). For instance, results from the National Survey of America's College Students (NSACS), which used the National Assessment of Adult Literacy (NAAL) to measure quantitative literacy, also showed students at four-year institutions outperforming their peers at two-year institutions (Baer et al 2006). The NSACS had approximately 1,800 graduating students at 80 randomly selected two-and four-year institutions as part of their sample.…”
Section: Performance Differences Across Subgroupssupporting
confidence: 80%
See 2 more Smart Citations
“…[15] However, in a national study, only 40% of students graduating from 4-year colleges were competent in the required knowledge and cognitive skills needed for academic writing. [16] Switzer and Perdue [17] noted that twothirds of the students who came to a graduate writing center lacked the skills to conduct a comprehensive literature search and to write academically.…”
Section: Literature Reviewmentioning
confidence: 99%